H-ATLAS: estimating redshifts of Herschel sources from sub-mm fluxes - Pearson, E; Eales, S; Dunne, L; Gonzalez-Nuevo, J; Maddox, S; Aguirre, J; Baes, M; Baker, A; Bourne, N; Bradford, C; Clark, C; Cooray, A; et al. (2013)
Upon its completion, the Herschel Astrophysics Terahertz Large Area Survey (H-ATLAS) will be the largest sub-millimetre survey to date, detecting close to half-a-million sources. It will only be possible to measure spectroscopic redshifts for a small fraction of these sources. However, if the rest-frame spectral energy distribution (SED) of a typical H-ATLAS source is known, this SED and the observed Herschel fluxes can be used to estimate the redshifts of the H-ATLAS sources without spectroscopic redshifts. In this paper, we use a sub-set of 40 H-ATLAS sources with previously measured redshifts in the range 0.5 < z < 4.2 to derive a suitable average template for high-redshift H-ATLAS sources. We find that a template with two dust components (Tc = 23.9K, Th = 46.9K and ratio of mass of cold dust to mass of warm dust of 30.1) provides a good fit to the rest-frame fluxes of the sources in our calibration sample. We use a jackknife technique to estimate the accuracy of the redshifts estimated with this template, finding a root mean square of Δz/(1 + z) = 0.26. For sources for which there is prior information that they lie at z > 1, we estimate that the rms of Δz/(1 + z) = 0.12. We have used this template to estimate the redshift distribution for the sources detected in the H-ATLAS equatorial fields, finding a bimodal distribution with a mean redshift of 1.2, 1.9 and 2.5 for 250, 350 and 500 μm selected sources, respectively. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.